Scientific Mapping of Elderly Food Studies: A Bibliometric Approach - Nafisah Eka Puteri; Muhammad Irfan Febriansyah (Universitas Teuku Umar, 2024)
As the global population ages, there is a growing emphasis on addressing the dietary needs and overall well-being of older individuals. Bibliometric analysis of existing literature on food innovation for the elderly helps identify research trends and gaps, guiding future exploration to better meet the nutritional needs and preferences of this population. The aim of this research is to examine the literature on food and nutrition for older adults through bibliometric analysis. Data was gathered on April 19th, 2024, from the Scopus database by using the search term